Adverse Obstetric Outcomes in Women with Previous Cesarean for Dystocia in Second Stage of Labor - Jastrow, Nicole; Demers, Suzanne; Gauthier, Robert J.; Chaillet, Nils; Brassard, Normand; Bujold, Emmanuel (American Journal of Perinatology, 2013)
Objective To evaluate obstetric outcomes in women undergoing a trial of labor (TOL) after a previous cesarean for dystocia in second stage of labor.Methods A retrospective cohort study of women with one previous low transverse cesarean undergoing a first TOL was performed. Women with previous cesarean for dystocia in first stage and those with previous dystocia in second stage were compared with those with previous cesarean for nonrecurrent reasons (controls). Multivariable regressions analyses were performed.Results Of 1655 women, those with previous dystocia in second stage of labor (n = 204) had greater risks than controls (n = 880) to have an operative delivery [odds ratio (OR): 1.5; 95% confidence intervals (CI) 1.1 to 2.2], shoulder dystocia (OR: 2.9; 95% CI 1.1 to 8.0), and uterine rupture in the second stage of labor (OR: 4.9; 95% CI 1.1 to 23), and especially in case of fetal macrosomia (OR: 29.6; 95% CI 4.4 to 202). The median second stage of labor duration before uterine rupture was 2.5 hours (interquartile range: 1.5 to 3.2 hours) in these women.Conclusion Previous cesarean for dystocia in the second stage of labor is associated with second-stage uterine rupture at next delivery, especially in cases of suspected fetal macrosomia and prolonged second stage of labor.
Keywords: pregnancy; vaginal birth after cesarean; uterine rupture; labor dystocia